Evaluation of trabecular bone changes according to the type of prosthesis in patients using bisphosphonates: a retrospective study - Begüm Ünlü Kurşun; Ender Akan (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The objective of the study was to retrospectively compare the fractal size values calculated in the trabecular bone according to the type of complete removable denture, removable partial denture, and partial fixed prosthesis between patients using bisphosphonates and healthy patients, retrospectively. Panoramic radiographs of a total of 200 patients, (100 using bisphosphonates,100 control group), were taken from the right and left molar regions before and after treatment with 72 × 72 pixels. The fractal dimension (FD) was computed by using ImageJ Software using the box-counting method on the images obtained. There was an interaction effect between the trabecular bone change-patient group-the type of prosthesis used and the parameters of the area (p < 0.05). In patients using complete removable dentures and removable partial dentures in the maxilla and mandibula in the molar region, a greater decrease in FD values was observed in the control group than in the patient group using bisphosphonates. An increase in FD values over time was observed in the patient group using bisphosphonates with partial fixed maxillary and mandibular prostheses compared to the control group. Partial fixed prostheses should be preferred primarily instead of complete removable or removable partial dentures in patients using bisphosphonates to prevent osteonecrosis due to dental trauma.